Urgensi Belajar Dalam Perspektif Al-Qur’an Surat Al-Alaq Ayat 1-5 Menurut Tafsir Ibnu Katsir - Taufik Mukmin (El-Ghiroh : Jurnal Studi Keislaman, 2016)
Prophet Muhammad get the first revelation of the Al-'Alaq 1-5; "Read the name of the Lord who made". This verse does not mention the object of reading. Thus, the religious leaders in Medina interpret the word Iqro in the sense of reading, studying, deliver, and so forth. And because the object is public, then the object can include everything affordable, neither of which is the sacred literature that comes from God or not, whether it concerns the verses written and unwritten. According to Tafsir Ibn Kastir the content of the letter al-'Alaq verses 1-5 is that we are commanded to always learn to conduct an investigation into any one that we do not know, so we speak, evidence of the mercy of Allah. is that he has taught them through the Qur’an.